The sequence dependent machine set-up problem: a brief overview. (2008)
The Sequence Dependent Machine Setup Problem (MSP), a class of difficult problems in combinatorial optimization that is representative of a large number of important scientific and engineering problems, has been attracting much attention in recent times. In this study, literature and historical reviews of the MSP were carried out. Some recent developments were reviewed while possible future research directions were also highlighted